Outcomes of ventral hernia repair in patients of severe obesity: An experience from a tertiary care centre - Sonali Mittal; Arun Kumar; Jagadeep Ajmera; Surabhi Vyas; Sandeep Aggarwal (Journal of Minimal Access Surgery)
Introduction: Ventral hernia (VH) in patients with severe obesity poses a surgical challenge during bariatric surgery (BS). There is conflicting evidence regarding the optimal timing to perform a definitive VH repair (VHR). We present our experience in managing severely obese patients with VH. Patients and Methods: Sixty-seven severely obese patients with VH underwent a cross-sectional analysis of outcomes after BS and VHR. Outcomes were presented in terms of patients’ demographics, BS performed, timing of VHR and recurrence rates. Results: Sixty-seven patients were included in the study. Seven patients who presented with complicated hernia underwent a concomitant BS and VHR (Group 1) and the rest with uncomplicated hernia underwent a staged VHR (Group 2). The mean age of presentation was 45.2 (±11.5) years, with a female preponderance (male:female = 17.9:82.1). The mean defect size was 3.4 (1.6) cm. Majority of Group 1 patients underwent an anatomical repair while Group 2 patients underwent a mesh hernioplasty. The patients in Group 1 had a higher body mass index at the time of VHR (47.4 ± 12.7 vs. 33.7 ± 4.21 kg/m2). The rate of recurrence was also higher in Group 1 compared to Group 2 (42.9% vs. 3.3%) at a mean duration of 10.3 and 12 months, respectively. Conclusion: VHR in patients with severe obesity is challenging. The staged approach appears to be a safer option with acceptable recurrence rates compared to the concomitant approach. However, an individualised approach based on patient presentation should be followed for VHR in such patients.